ROS scavenging and ion homeostasis is required for the adaptation of halophyte Karelinia caspia to high salinity - Li, Cui; Mur, Luis A.J.; Wang, Qinghai; Hou, Xincun; Zhao, Chunqiao; Chen, Zhimin; Wu, Juying; Guo, Qiang (Frontiers in Plant Science, 2022)
The halophyte Karelinia caspia is not only fodder and medical values but also can remediate saline-alkali soils. Our previous study showed that salt-secreting by salt glands is one of main adaptive strategies of K. caspia under high salinity. However, ROS scavenging, ions homeostasis, and photosynthetic characteristics response to high salinity remains unclear in K. caspia. Here, physio-biochemical responses and gene expression associated with ROS scavenging and ions transport were tested in K. caspia subjected to 100-400 mM NaCl for 7 days. Results showed that both antioxidant enzymes (SOD, APX) activities and non-enzymatic antioxidants (chlorogenic acid, α-tocopherol, flavonoids, polyamines) contents were significantly enhanced, accompanied by up-regulating the related enzyme and non-enzymatic antioxidant synthesis genes (KcCu/Zn-SOD, KcAPX6, KcHCT, KcHPT1, Kcγ-TMT, KcF3H , KcSAMS and KcSMS) expression with increasing concentrations of NaCl. These responses are beneficial for removing excess ROS to maintain a stable level of H2O2 and O2- without lipid peroxidation damage in K. caspia response to high salt. Meanwhile, up-regulating expression of KcSOS1/2/3, KcNHX1, and KcAVP is linked to the Na+ was compartmentalized into vacuoles or excreted through slat glands in K. caspia. Notably, salt can improve the function of PSII that facilitate net photosynthetic rates, which is helpful to grow normally in high saline. Overall, the findings suggested that ROS scavenging systems and Na+/K+ transport is synergistically contributed to redox equilibrium, ions homeostasis, and the enhancement of PSII function, thereby conferring its high salt tolerance.